Islam - Esposito, John L. (Oxford University Press, 2005)
The Straight Path includes a new Epilogue by John Esposito in which he addresses the impact 9/11 and its aftermath have had on both the Muslim and non-Muslim world, discussing Islam's relationship to democracy and modernity and focusing more sharply on the origins and growth of extremism and terrorism in the name of Islam